Archaeological Finds of Jet from Norway - Heid Gjøstein Resi (Collegium Medievale, 2005)
The point of departure for this article is the find of half of a finger ring of jet from the archaeological excavations at VesleH jerkinn, Dovre, Oppland. The site is interpreted as a mountain lodge at the main trail over the mountains between eastern Norway and Nidaros (Weber 1986, Weber forthcoming). The site contains several buildings dated to the period 1Oth to the 13th century. The jet ring was found in a waste mound close to one of the buildings. Its closest parallels are found among the jet jewellery of supposed British origin from Norwegian Viking Age finds (Shetelig 1946). Gaming pieces and beads of jet from excavations of medieval towns, and beads from stave church sites show that the use of jet extended well into the Middle Ages. It is not clear whether these later finds indicate continuous contact westwards with the same supposed origins of jet as in the Viking Age, or if they originate from other areas.